2016
DOI: 10.3390/molecules21060567
|View full text |Cite
|
Sign up to set email alerts
|

Methyl Jasmonate: An Alternative for Improving the Quality and Health Properties of Fresh Fruits

Abstract: Methyl jasmonate (MeJA) is a plant growth regulator belonging to the jasmonate family. It plays an important role as a possible airborne signaling molecule mediating intra-and inter-plant communications and modulating plant defense responses, including antioxidant systems. Most assessments of this compound have dealt with post-harvest fruit applications, demonstrating induced plant resistance against the detrimental impacts of storage (chilling injuries and pathogen attacks), enhancing secondary metabolites an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
68
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 121 publications
(76 citation statements)
references
References 111 publications
6
68
0
2
Order By: Relevance
“…This kind effect of MeJA was reported by other researchers (Maciejewska & Kopcewicz, 2002;Reyes-Díaz et al, 2016).…”
Section: R Solanacearum Inoculation Modifies Expression Levels Of supporting
confidence: 84%
“…This kind effect of MeJA was reported by other researchers (Maciejewska & Kopcewicz, 2002;Reyes-Díaz et al, 2016).…”
Section: R Solanacearum Inoculation Modifies Expression Levels Of supporting
confidence: 84%
“…4,30 Thus, the effect of MeJA treatment on an increasing phenolic concentration in juice and flavedo of lemon fruit would lead to an enhanced antioxidant potential and health-beneficial effects. 18 Indeed, MeJA treatment of blackberry plants increased the effect of fruit extracts with respect to inhibiting cancer cell proliferation and inducing apoptosis in human lung cancer cells, 36 which was correlated with an increased phenolic concentration. In lemon fruit, a previous study has reported the effect of postharvest 10 μmol L -1 MeJA treatment on an increasing phenolic concentration in flavedo during storage as a result of an increase in PAL activity.…”
Section: Discussionmentioning
confidence: 98%
“…These phenolic compounds, together with ascorbic acid, are mainly responsible for the antioxidant properties attributed to lemon fruit, which not only depend on the concentration of each individual compound, but also on the interactions among them . Thus, the effect of MeJA treatment on an increasing phenolic concentration in juice and flavedo of lemon fruit would lead to an enhanced antioxidant potential and health‐beneficial effects . Indeed, MeJA treatment of blackberry plants increased the effect of fruit extracts with respect to inhibiting cancer cell proliferation and inducing apoptosis in human lung cancer cells, which was correlated with an increased phenolic concentration.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations